Edukasi Penanggulangan Banjir Melalui KKN Mahasiswa Stisipol Candradimuka, Di Kelurahan Sako Untuk Mewujudkan Program Kampung Iklim Sigap, Cerdas Dan Sehat - Ardiansyah (Yayasan Kajian Riset dan Pengembangan RADISI, 2021)
Indonesia is a country that is prone to natural disasters. Almost all types of disasters that have occurred in Indonesia. Indonesia is ranked fifth in the world for the highest number of deaths caused by natural disasters. This is an